Acetaminophen inhibits hemoprotein-catalyzed lipid peroxidation and attenuates rhabdomyolysis-induced renal failure - Boutaud, Olivier (National Academy of Sciences, 2010)
Hemoproteins, hemoglobin and myoglobin, once released from cells can cause severe oxidative damage as a consequence of heme redox cycling between ferric and ferryl states that generates radical species that induce lipid peroxidation. We demonstrate in vitro that acetaminophen inhibits hemoprotein-induced lipid peroxidation by reducing ferryl heme to its ferric state and quenching globin radicals. Severe muscle injury (rhabdomyolysis) is accompanied by the release of myoglobin that becomes deposited in the kidney, causing renal injury. We previously showed in a rat model of rhabdomyolysis that redox cycling between ferric and ferryl myoglobin yields radical species that cause severe oxidative damage to the kidney. In this model, acetaminophen at therapeutic plasma concentrations significantly decreased oxidant injury in the kidney, improved renal function, and reduced renal damage. These findings also provide a hypothesis for potential therapeutic applications for acetaminophen in diseases involving hemoprotein-mediated oxidative injury.